Observation of stochastic resonance in percolative Josephson media - Glukhov, A. M.; Sivakov, A. G.; Ustinov, A. V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2002)
Measurements of the electrical response of granular Sn-Ge thin films below the superconducting transition temperature are reported. Addition of an external noise to the magnetic field applied to the sample is found to increase the sample voltage response to a small externally applied ac signal. The gain coefficient for this signal as well as the signal-to-noise ratio displays clear maxima at particular noise levels. We interpret these observations as a stochastic resonance in the percolative Josephson media that occurs close to the percolation threshold.